1988
DOI: 10.1007/bf02302619
|View full text |Cite
|
Sign up to set email alerts
|

Meander of the Kuroshio front and current variability in the East China Sea

Abstract: Abstract:To investigate the fluctuation of the t(uroshio front, moored current meters were deployed near the shelf break and on the continental slope in the East China Sea, northwest of Okinawa Island, during a period from 25 June to 22 July 1984. Two mooring arrays were deployed on the slope of about 800m water depth (under the Kuroshio), about 30km apart along the path of the Kuroshio. Another two arrays were set near the shelf break of about 300m water depth.The fluctuation of current on the slope is found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 2 publications
5
21
0
Order By: Relevance
“…Frontal waves of similar frequencies have been reported in other coastal areas in Japan: in the East China Sea (Sugimoto et al 1988;Qiu et al 1990;James et al 1999), in the Tokara Strait (Qiu et al 1990;Maeda et al 1993;Feng et al 2000), south of Shikoku (Awaji et al 1991), near the separation point of the Kuroshio to the Kuroshio Extension (Itoh and Sugimoto 2008), and in the Kuroshio Extension (Tracey et al 2012). Frontal wave disturbances have been also found in the Gulf Stream (Lee and Atkinson 1983;Tracey and Watts 1986;Oey 1988;Savidge 2004).…”
Section: Summary and Discussionsupporting
confidence: 72%
“…Frontal waves of similar frequencies have been reported in other coastal areas in Japan: in the East China Sea (Sugimoto et al 1988;Qiu et al 1990;James et al 1999), in the Tokara Strait (Qiu et al 1990;Maeda et al 1993;Feng et al 2000), south of Shikoku (Awaji et al 1991), near the separation point of the Kuroshio to the Kuroshio Extension (Itoh and Sugimoto 2008), and in the Kuroshio Extension (Tracey et al 2012). Frontal wave disturbances have been also found in the Gulf Stream (Lee and Atkinson 1983;Tracey and Watts 1986;Oey 1988;Savidge 2004).…”
Section: Summary and Discussionsupporting
confidence: 72%
“…Studies of frontal disturbances of the Kuroshio in upstream regions of our study showed similar periods as the 11-20 days for the East China sea (Eguchi et al, 1982;Shibata, 1983;Sugimoto et al, 1988;Qiu et al, 1990), 20 and 15 to 30 days for the Tokara Strait (Nagata and Takeshita, 1985;Akiyama and Ameya, 1991), and 20 and 50 days for the Enshu-nada and Kumano-nada seas (Kimura and Sugimoto, 1983;Kasai et al, 1993). Sugimoto et al (1992a) observed that streamers spiraling around the WCR 86B, in the Perturbed Area east of Japan, had a generation frequency from the Kuroshio Extension of once in 20 days and 40-50 days.…”
Section: Short-term and Seasonal Variability Of The Northward Spreadsupporting
confidence: 82%
“…The subsurface boundary of the front may slope down to the offshore above the shelf slope keeping a horizontal shape similar to that at the surface. Such an extension of the front is also supported from the fact that the countercurrent of the Kuroshio has been observed in near-bottom water above the shelf slope (Sugimoto et al, 1988;Gohda et al, 1992). The cyclonic curves of the flow along the front also has a chance of spinning up cyclonic eddies (Lee et al, 1981).…”
Section: Discussionmentioning
confidence: 84%
“…The Kuroshio flowing northeastward along the East China Sea shelf slope is known to generate a meandering thermo-haline front at the shelf break and a countercurrent directed to the SW in near-bottom water above the shelf slope (Sugimoto et al, 1988;Qiu et al, 1990;Gohda et al, 1992). From the water-mass and mixing-depth analyses of silica, Ito et al (1994) provided us an evidence that the intermediate water of the Kuroshio in the depth range of 100-400 m is upwelled into the East China Sea continental shelf.…”
Section: Introductionmentioning
confidence: 99%